Selective High Performance Liquid Chromatographic Determination of Amodiaquine and Artesunate in bulk and pharmaceutical formulation - P. S. Jain,A. J. Chaudhari and S. J. Surana (Journal of Applied Pharmaceutical Science, 2013)
Aim of the study was to develop a new selective high-performance liquid chromatography (HPLC) method for the quantification of amodiaquine and artesunate in bulk and pharmaceutical dosage form. The HPLC analysis was performed on the LCGC Qualisil C 8 (5 µm, 250 mm × 4.6 mm i.d.) column in isocratic mode, at 300C temperature using a mobile phase consisting of Acetonitrile: phosphate buffer (70:30, v/v) at a flow rate of 0.8 ml/min. The detection was carried out at 254nm for amodiaquine and 221nm for artesunate. The retention time for AMQ and ART were found to be 2.8 min. and 5.6 min. respectively. The method was validated for precision, recovery, robustness, specificity, and detection and quantification limits, in accordance with International Conference on Harmonization guidelines. Linearity was observed in the concentration range from 2-12 µg/ml (r2=0.998) for AMQ and for ART 0.2-1.2 mg/ml (r2=0.998). The limit of detection and quantification of AMQ were 0.07 µg/ml and 0.21 µg/ml respectively. While for ART it was 0.044 mg/ml and 0.133 mg/ml, respectively. The method has been successively applied for the determination of AMQ and ART in tablets. There was no interference from the excipients commonly present in the tablets. The drug content was found to be 100.83 % for AMQ and 98.63 for ART. Accuracy of the method was studied by the recovery studies at three different levels 80 %, 100 % and 120 %. The % recovery was found to be within the limits of the acceptance criteria with average recovery of 98.55–101.46% for AMQ and 99.48–101.60% for ART. The % RSD below 2.0 shows the high precision of proposed method. The above method was a rapid and cost-effective quality-control tool for routine analysis of amodiaquine and artesunate in bulk and in pharmaceutical dosage form.
Keywords: HPLC, Method Validation, Quantitative Determination